Model Keterkaitan Inovasi Produk, Citra Merek, Persepsi Nilai dan Intensi Pembelian Produk Kerajinan Tenun Kubang di Sumatera Barat - Ratni Prima Lita; Ranny Fitriana Faisal; Devi Yulia Rahmi; Mulia Gusmai; Meuthia Meuthia (Jurnal Manajemen dan Kewirausahaan, 2019)
The aims of this study are to determine and analyze the relationship product innovation, brand image, perceived value and purchase intention in the craft of weaving in the district of Kubang. This study uses a purposive sampling technique with 145 respondents of weaving crafts. The criteria of the sample are consumers (individuals) who know the products weaving. The data  analysis uses Partial Least Square-SEM with software Smart PLS. The result of this study shows that : 1) brand image has a significant effect on the perceived value, 2) product innovation has a significant effect on the brand image,  3) perceived value has a significant effect on the purchase intention, and 4) brand image and product innovation are not able to provide a significant effect on purchase intention.https://doi.org/10.26905/jmdk.v7i2.3290